Implantation system brine recover from some chemical treatment tanks in a Plant Chlor - Alkali (2016)
Objectives: This study establishes aimed at recovering the brine flowing with sewage sludge to decrease the concentration of chlorides and reduce salt intake. Methods/Statistical Analysis: A piping system taking into account the characteristics of the sludge, which served as the basis for determining the loss of brine in the effluent, make the necessary calculations for the piping systems to develop and to transport the sludge from the point was raised unloading to the recovery site. considered the issue sis sizing based on the measurement of levels, distance the pipe section to place, make the hydraulic study and plans isometric system was developed. Findings: With the recovery of brine, it manages to reduce consumption of 7.11 tons of salt daily at the plant, leading to savings of 35,539.6 bolivars per year for salt intake. Application/Improvements: When recovering the drained brine the impact this causes for chlorine soda plant, the central plant effluent and receiving water body (Lake Maracaibo) is decreased.